Industrial Logistics Performance of Thai Industry - Jangkrajarng, Varattaya; Sopadan, Apichat; Y.Tippayawong, Korrakot; Manopiniwes, Wapee; Santiteerakul, Salinee; Ramingwong, Sakgasem (International Journal of Engineering and Technology, 2018)
Industrial Logistics Performance Indicators (ILPI) is used as an assessing tool for 27 logistics performance, developed for Thai industry.  From 1,644 companies in the database collection, the study aims at providing individuality view of logistics performance of 5 industries, i.e., food, chemicals, rubber and plastic, machinery and equipment and electrical industries.  As the industry and products vary, the paper is to explore key logistics characteristics as the over- and under- performance, outstanding from others.  The findings are indicatives that each industry focus and pay attentions on which performances.  The finding is also suggestive if ones must understand the industry or wish to support the industry in any measures.